Positive Attitude of Authoritative Teachers in Their Relationships with Students - Angga Mahyuda Sinaga; Dorlan Naibaho (edujavare, 2024)
The teacher's attitude includes emotional aspects, attitudes and values ​​that are owned and demonstrated in the learning process. Teachers who have a good attitude can create a positive learning environment, motivate students, and build good relationships between teachers and students. First, empathy is a key element in teachers' affective attitudes. Teachers who can understand students' feelings and experiences can respond better to their needs. Second, patience and tolerance are other characteristics. Patient teachers can provide additional support to students who are experiencing difficulties, while tolerance helps in respecting diversity in the classroom. Third, a positive attitude and motivation are also important. Teachers who demonstrate a positive spirit can inspire students, create an environment that supports active learning, and encourage students' desire to learn. Fourth, professionalism in communicating and interacting with parents and school staff also reflects the teacher's strong affective attitude. Open and collaborative communication strengthens relationships between schools, teachers, and parents, creating effective educational teams. Overall, teachers' affective attitudes are not only about knowledge and teaching skills, but also involve emotional and social dimensions that play an important role in shaping meaningful learning experiences for students.